Effects of Beating and Recycling on Strength of Pulp Fibers and Paper - Somwang Khantayanuwong (Agriculture and Natural Resources, 2002)
The effects of beating and recycling treatment on strength of pulp fibers and handsheets were ascertained in this study. The zero-span tensile strength of handsheets, which corresponds to strength of fibers as such, tended to increase by beating and recycling treatment. Therefore, the decrease in the tensile strength of recycled handsheets was caused by the decrease of interfiber bonding strength as explainable by using the Page equation. Because the recycling treatment did not affect the specific strength of interfiber bonding, the decreased strength of interfiber bonding solely stemmed from the decreased interfiber-bonded area.